A Theoretical Analysis of the Economics of Efficiency, Bargaining and Welfare Distribution - Jean-Paul Chavas; Mingcong Pan (An Overview on Business, Management and Economics Research Vol. 8, 2024)
This chapter develops a joint analysis of efficiency and distributional issues in an economy in general equilibrium with a focus on bargaining under bounded rationality. We propose evolutionary schemes representing bargaining, where each step of the bargaining process identifies who is willing to make a concession depending on the relative perceived cost of bargaining failure. Our analysis relies on evolutionary strategies based on the Nash-Harsanyi bargaining model, but we go beyond the Nash-Harsanyi model by generalizing it with ordinal preferences as well as allowing for inefficient bargaining agreements. We show that our evolutionary schemes converge to bargaining agreements under general conditions. The analysis covers the case where the bargaining agreement is inefficient as well as the case where the bargaining process converges to an efficient allocation located on the Pareto utility frontier. We show that the outcome of the bargaining process can be represented by the simple maximization of a “generalized Nash product.” We explore the implications of bargaining agreements for income distribution. Finally, we discuss our model’s insights in analyzing the performance of an economy, emphasizing the roles of preferences, decentralization, and public goods. In the presence of strong linkages between threat points and welfare distribution, the design and implementation of conflict resolution mechanisms need further investigations.